2018
DOI: 10.1111/1750-3841.14091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dipping and Vacuum Impregnation Coating Techniques with Alginate Based Coating on Physical Quality Parameters of Cantaloupe Melon

Abstract: Type of edible coating technique and the parameters used significantly affect the physical quality characteristics of coated food products. The work presented produced more technical information concerning dipping and vacuum impregnation coating techniques, along with evaluating the effects of various coating parameters with several levels. The results revealed that vacuum impregnation technique is a successful coating method; however the effects should be carefully assessed for each product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 30 publications
(42 reference statements)
2
24
0
Order By: Relevance
“…On the other hand, CH-coated fruit presented the highest and stable firmness values during the total storage time (p < 0.05; Table 1). A similar effect has been reported in previous studies [24,25,37]. Compared to previous studies, lower firmness values have been reported on fresh-cut cantaloupe coated with pectin [23], cellulose [38], carboxymethylcellulose [25], and alginate [24].…”
Section: Juice Leakage Firmness and Color Testssupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, CH-coated fruit presented the highest and stable firmness values during the total storage time (p < 0.05; Table 1). A similar effect has been reported in previous studies [24,25,37]. Compared to previous studies, lower firmness values have been reported on fresh-cut cantaloupe coated with pectin [23], cellulose [38], carboxymethylcellulose [25], and alginate [24].…”
Section: Juice Leakage Firmness and Color Testssupporting
confidence: 87%
“…A similar effect has been reported in previous studies [24,25,37]. Compared to previous studies, lower firmness values have been reported on fresh-cut cantaloupe coated with pectin [23], cellulose [38], carboxymethylcellulose [25], and alginate [24]. Conversely, higher values have been reported using multilayered ECs with the formula CH/pectin/trans-cinnamaldehyde [8].…”
Section: Juice Leakage Firmness and Color Testssupporting
confidence: 84%
See 1 more Smart Citation
“…Dip coating of zirconia in the sol-gel solution followed by sintering was reported by Matsuda et al 28) and fabrication of the 45S5 BG coating by dip coating method in the sol-gel solution and its apatite formation ability in the simulated body fluid (SBF) on Mg substrates are reported previously 29,30) . In the present study the 45S5 BG coating layer fabricated by vacuum-assisted dipping method 31) on the zirconia surface which has been named vacuum soldipping method. This technique has several advantages such as fast coating procedure, suitable coverage ability, sol impregnation, strong adhesion of BG to the substrate surface and fabrication of BG in low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Foam application is used for those film-forming solutions that come in the form of an emulsion and requires the existence of a foaming agent; the coating is obtained with the help of compressed air; brushing is used for full application of the coating on the product surface; and a spray is generally used when the films are thin or when the coating is applied only on one side of the product [55]. The vacuum-impregnation method is used to enrich a product with vitamins or minerals [56]. Films are applied by the method of casting or extrusion when looking at composite or multilayer films [57].…”
Section: Sodium Alginate-a Basic Component Of Packaging Materials In mentioning
confidence: 99%